Halaqah Sebagai Model Alternatif Pembentukan Karakter Siswa - Sudrajat Sudrajat (Institut Agama Islam Negeri Purwokerto, 2018)
The empirical condition of character problem of young generation, especially among students, has become the main concern of Indonesia. Schools become a strategic place to seed good character and eliminate existing moral anomalies. Of the various programs and models of character education, student halaqah can be used as an alternative model. With various values of urgency and superiority, halaqah is considered effective for the formation of student character. This will be accomplished by sustained systematic management of halaqah covering program planning, team building, socialization, program implementation, guidance to evaluation and follow-up.